An assessment of building vulnerability to a tsunami in the Galle coastal area, Sri Lanka - Sathiparan, N. (Elsevier, 2020)
Tsunami vulnerability assessment is the initial step for effective planning and implementation of tsunami risk reduction. Whilst the high tsunami risk of the Galle coastal area is well known, the structural vulnerability to tsunami hazards has never been assessed. This paper presents tsunami vulnerability for structures, relative vulnerability indexes, and vulnerable areas in Galle city, Sri Lanka. To develop the relative vulnerability index map, data on 705 buildings in terms of attributes of the building, protection of the building, and depth of the water flow at the building location were obtained from field surveys. The results of the structural vulnerability assessment show that if the 2004 Indian Ocean tsunami were to occur today, 35% of the buildings would be affected in the Galle coastal area and when we consider the 100 m buffer zone, this value increases to 56%. Buildings with minor vulnerability constituted around only 3% inside the 100 m buffer zone.
Keywords: tsunami; Inundation